The Experience of Sailboat Crews in Dealing with Emergencies during the Accident in Labuan Bajo, East Nusa Tenggara, Indonesia: A Phenomenology - Yuliana Reginaldis Rosali Krowa; Retty Ratnawati; Yati Sri Hayati (International Journal of Science and Society, 2020)
Ship accidents create emergencies and affect victims, both physically and psychologically. Human error and extreme weather are still the main causes of ship accidents. The crew of the ship, especially the skipper, has an important role and responsibility in ensuring the safety and security of passengers while on the ship. This study is a phenomenology study that aimed to explore the experience of the sailboat crew in dealing with an emergency during an accident in Labuan Bajo, East Nusa Tenggara, Indonesia. Data collection using in-depth interviews with six crew members who have experienced accidents with tourist passengers. The interview result was recorded and transcribed by the researcher and data were then analysed using Interpretative Phenomenological Analysis (IPA) which consisted of six steps of analysis (Reading and re-reading, Initial Noting, Developing Emergent Themes, Searching for Connections Across Emergent Themes, Moving the Next Cases, and Looking for Patterns Across Cases). The results of this study indicate that the crew always tries to save passengers by utilizing the safety equipment available onboard. Although other results indicate that the crew felt that the ship accident was a disaster that occurred outside of the human will, or was not crew negligence.